Gasification process as a complex method of sewage sludge treatment = Zgazowanie jako kompleksowa metoda zagospodarowania osadów ściekowych - Werle, Sebastian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Today, there is a rising interest in many countries in ?traditional? (e.g. agro and forest) biomass and waste biomass (e.g. sewage sludge) utilization processes (e.g. combustion, co-combustion, gasification and pyrolysis). During the last twenty years, there has been a major change in the way that sludge is disposed.
Keywords: zgazowanie osadów ściekowych; zagospodarowanie osadów ściekowych; osady ściekowe; biomasa odpadowa; gasification; sewage sludge; sludge management